2017
DOI: 10.1080/00981389.2016.1277823
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in Suriname

Abstract: Background: Low health literacy is an independent predictor of cardiovascular mortality. However, data on health literacy in low-and middle-income countries are scarce. Therefore, we assessed the level of health literacy in Suriname, a middleincome country with a high cardiovascular mortality. Methods: We estimated health literacy in a convenience sample at an urban outpatient center in the capital and at a semirural health center, using the validated Rapid Estimate of Adult Literacy in Medicine adapted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Most people were interviewed in health services (70 studies; n = 14,570; 60.9%) [ 12 17 , 19 , 21 – 23 , 25 38 , 40 , 41 , 43 45 , 47 – 67 , 69 , 71 , 73 – 78 , 81 86 , 89 , 91 – 95 ]. The predominant population was general population (15 studies; n = 9,112; 38.1%) [ 18 , 20 , 22 , 24 , 26 , 35 , 41 , 44 , 52 , 63 , 64 , 71 , 72 , 80 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people were interviewed in health services (70 studies; n = 14,570; 60.9%) [ 12 17 , 19 , 21 – 23 , 25 38 , 40 , 41 , 43 45 , 47 – 67 , 69 , 71 , 73 – 78 , 81 86 , 89 , 91 – 95 ]. The predominant population was general population (15 studies; n = 9,112; 38.1%) [ 18 , 20 , 22 , 24 , 26 , 35 , 41 , 44 , 52 , 63 , 64 , 71 , 72 , 80 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the different age and formal education presentation formats, the results were shown narratively for studies that reported mean or median. Four studies ( n = 729; 3.0%) [ 41 , 46 , 68 , 85 ] evaluated a population under 30 years of age, and 35 studies ( n = 8,315; 34.8%) [ 12 , 14 , 16 , 25 , 26 , 29 , 31 , 32 , 35 , 40 , 44 , 45 , 48 , 50 , 51 , 53 , 54 , 56 , 57 , 60 , 62 – 64 , 66 , 67 , 69 , 71 , 79 , 82 , 86 , 89 , 90 , 92 , 93 , 95 ] assessed HL in adults with an average age between 30 and 60 years of age. 25 studies had a population with an average age above 60 years ( n = 5,870; 24.5%) [ 13 , 15 , 17 , 21 , 24 , 28 , 33 , 37 39 , 42 , 49 , 55 , 59 , 61 , 65 , 70 , 75 77 , 81 , 83 , 84 , 88 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found no studies that evaluated national levels of health literacy in Latin American countries. Table 1 shows considerable variation of measurement approaches in regional studies, with adequate health literacy ranging from 5.0% to 73.3%, although assessments did not always use the same scale, and definitions of adequate health literacy were inconsistent (7)(8)(9)(10)(11)(12)(13)(14). Condition-specific assessments have also been evaluated.…”
Section: Current State Of Health Literacy In Latin Americamentioning
confidence: 99%
“…Studies evaluating health literacy often did so in association with concerns about prevalent diseases that cause high morbidity and mortality, like cardiovascular disease in Suriname, diabetes in Brazil, and tuberculosis in Peru (9,13,14). This is important, as adequate health literacy may enable people to engage in positive behaviors related to modifiable risk factors for non-communicable diseases and help people recognize and slow the transmission and progression of communicable diseases.…”
Section: Current State Of Health Literacy In Latin Americamentioning
confidence: 99%
“…Assim, melhorar o letramento em saúde sustenta o avanço nos ODS, incluindo a erradicação da pobreza e da fome, educação de qualidade e redução das desigualdades. A consecução dos ODS exigirá prioridade ao desenvolvimento do letramento em saúde por parte de todos dos governantes, formuladores de políticas, organizações de saúde e profissionais para Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.17 Como um dos determinantes de saúde mais importantes da prevenção de doenças crônicas não transmissíveis (HAGHDOOST et al, 2019), o letramento em saúde é pré-requisito para a implementação adequada de estratégias preventivas (DIEMER et al, 2017); é ponto chave para o acesso adequado aos cuidados de saúde e, consequentemente, para a redução de custos (PALUMBO, 2017). É ainda considerado fator de risco modificável das desigualdades socioeconômicas em saúde (STORMACQ; VAN DEN BROUCKE;WOSINSKI, 2019) e apontado como meta de saúde pública para melhorar a promoção e os resultados de saúde (PARNELL et al, 2019).…”
Section: Introductionunclassified